Use of Ketamine-Propofol ‘Ketofol’ versus Ketamine- Midazolam for Procedural Sedation and Analgesia - Maruf, Abdullah Al; Haque, M Masudul; Hossain, Md Mozaffer; Nazrina, Sayeda (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Procedural sedation and analgesia (PSA) is useful technique for unpleasant surgical, diagnostic and interventional procedures while maintaining cardiorespiratory function. Unfortunately, at this time no single agent available that complete PSA successfully, so combinations of different drugs used at varying does to achieve the desired goal. Objectives: The purpose of this study is to observe the effectiveness of combination of ketamine and propofol (Ketofol) in comparison with ketamine midazolam combination in patients undergoing procedural sedation and analgesia (PSA) for short elective and emergency surgeries. Methods: One hundred patient of both sex, ASA grade I & II, age 18 to 50 years were scheduled to undergo different short surgical procedures (less than 1 hour) were randomly assigned into 2 groups. In Group KP (n=50) recieved Ketamine & Propofol (1:1) and Group KM (n=50) received Ketamine and midazolam at the discretion of the anaesthesiologist by using titrated aliquots for completion of the procedure. All perioperative vital parameters, events, complications, recovery status, and cost of sedation regimen were recorded and subsequently analyzed. Results: The two groups were fairly comparable regarding demographic and preoperative data. Group KP remain more stable than Group KM haemodynamicaly; heart rate, systolic blood pressure, diastolic blood pressure and mean blood pressure were significantly higher in Group KM than Group KP during procedure at 5, 10, 15, 20 and 25 minutes (p<0.01). Recovery time was 19.71±7.58 (mean±SD) minutes in Group KP and 32.25±8.91 (mean±SD) minutes in Group KM which was significantly higher (P<0.01). Cost (taka) of sedation regimen was significantly higher in Group KP than Group KM (P<0.01). Regarding sedition related side effects; incidences of hypertension (systolic BP more than 30% of baseline record) was found 1(2%) in Group KP and 5(10%) was found in Group KM and difference was statistically significant (P<0.01). Other notable side effects were desaturation (SpO2 less than 93 %), airway misalignment, vomiting and agitation were almost similar and differences between two groups were statistically not significant. Conclusion: Combination of ketamine and propofol ((ketofol) appeared to be a safe and efficacious during procedural sedation and analgesia regarding haemodynamic stability and short recovery period in comparison with ketamine midazolam combination for short surgical procedures. Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 19-28